Design and simulation of 50 nm vertical double-gate MOSFET (VDGM) - Saad, Ismail; Ismail, Razali (2006)
The paper demonstrate the design and simulation study of 2D vertical double- gate MOSFET (VDGM) with an excellent short channel effect (SCE) characteristics. With the gate length of 50 nm, body doping of 3.5 times 1018 cm-3 and oxide thickness, TOX = 2.5 nm, a good drive current ION of 7 muA/mum and a low off-state leakage current IOFF of 2 pA/mum was explicitly shown. Besides that, the subthreshold characteristics also highlighted a reasonably well-controlled SCE with subthreshold swing SubVT = 89 mV/decade and threshold voltage VT = 0.56 V. The analysis of body doping effects for SCE optimization and drive current trade-off was also done for an overall investigation and limit of the VDGM.